PERANCANGAN SISTEM BASISDATA ERP (ENTREPRISE RESOURCE PLANNING) PENDIDIKAN TINGGI DENGAN METODE SOA (SERVICES ORIENTED ARCHITECTURE) - Anief Rufiyanto (Universitas Pandanaran, 2015)
ERP system for higher education is a software in order to accommodate the resource needs in an educational institution. ERP (entreprise resource planning) is an information system companies that designed to coordinate all resource, information and activities that need for complete business process. ERP system based in database, at general and software plan modular. Primal condition from ERP system is integration. Integration, it’s mean to unite various need in one software in one logical database. Database as base application, built consideringly base SOA (service oriented architecture). SOA be software planning that designed in such a manner, up to there flexible moment development phase system and or integration process, where prepare loosely-integrated suit of services that at use in various business domain. The system assesses the development of the utilization of existing resources in an educational institution. Because after all educational institutions should have policies not only make a profit as an economic enterprise. Implemented starting from the data of teachers, students, subject matter to, evaluation of students' learning, including the annual report. Design and implementation of system 3 components, namely: People (human resources and student), Process (interaction of the learning process and the system) and Product (learning content, output).Keywords: higher education, ERP, database, SOA